Pterostilbene attenuates microglial inflammation and brain injury after intracerebral hemorrhage in an OPA1-dependent manner - Wu, Yang; Hu, Qing; Wang, Xiaoliang; Cheng, Hongbo; Yu, Jiegang; Li, Yang; Luo, Jianing; Zhang, Qingjiu; Wu, Jianliang; Zhang, Gengshen (Frontiers in Immunology, 2023)
Microglial activation and subsequent inflammatory responses are critical processes in aggravating secondary brain injury after intracerebral hemorrhage (ICH). Pterostilbene (3’, 5’-dimethoxy-resveratrol) features antioxidant and anti-inflammation properties and has been proven neuroprotective. In this study, we aimed to explore whether Pterostilbene could attenuate neuroinflammation after experimental ICH, as well as underlying molecular mechanisms. Here, a collagenase-induced ICH in mice was followed by intraperitoneal injection of Pterostilbene (10 mg/kg) or vehicle once daily. PTE-treated mice performed significantly better than vehicle-treated controls in the neurological behavior test after ICH. Furthermore, our results showed that Pterostilbene reduced lesion volume and neural apoptosis, and alleviated blood-brain barrier (BBB) damage and brain edema. RNA sequencing and subsequent experiments showed that ICH-induced neuroinflammation and microglial proinflammatory activities were markedly suppressed by Pterostilbene treatment. With regard to the mechanisms, we identified that the anti-inflammatory effects of Pterostilbene relied on remodeling mitochondrial dynamics in microglia. Concretely, Pterostilbene reversed the downregulation of OPA1, promoted mitochondrial fusion, restored normal mitochondrial morphology, and reduced mitochondrial fragmentation and superoxide in microglia after OxyHb treatment. Moreover, conditionally deleting microglial OPA1 in mice largely countered the effects of Pterostilbene on alleviating microglial inflammation, BBB damage, brain edema and neurological impairment following ICH. In summary, we provided the first evidence that Pterostilbene is a promising agent for alleviating neuroinflammation and brain injury after ICH in mice, and uncovered a novel regulatory relationship between Pterostilbene and OPA1-mediated mitochondrial fusion.